Do Wage Subsidies Work in Boosting Economic Inclusion? Evidence on Effect Heterogeneity in Austria - Rainer Eppel; Helmut Mahringer (Austrian Institute of Economic Research (WIFO), 2013)
We construct two matching scenarios to estimate the long-term impact of targeted wage subsidies in Austria on the subsequent labour market integration of previously unemployed participants. Even if substantial dead-weight loss is taken into account, the treated experience a significant increase in employment in the seven years from program start and spend considerably less time in unemployment and out of the labour force than similar nonparticipants. The effect increases with age and with pre-treatment unemployment duration. It is particularly large for older workers and the long-term unemployed. Hence, wage subsidies are particularly effective in helping disadvantaged unemployed individuals back into employment. Cumulated earnings rise significantly for the treated as a result of their relative increase in employment. Participation in the program does, however, not exert a positive influence on the quality of jobs in terms of the average wage level.
Keywords: 330; Arbeitsmarktintegration; Lohnsubvention; Beschäftigungseffekt; Österreich